2009
DOI: 10.1897/08-207.1
|View full text |Cite
|
Sign up to set email alerts
|

Benthic nutrient sources to hypereutrophic Upper Klamath Lake, Oregon, USA

Abstract: Three collecting trips were coordinated in April, May, and August 2006 to sample the water column and benthos of hypereutrophic Upper Klamath Lake (OR, USA) through the annual cyanophyte bloom of Aphanizomenon flos-aquae. A pore-water profiler was designed and fabricated to obtain the first high-resolution (centimeter-scale) estimates of the vertical concentration gradients of macro- and micronutrients for diffusive-flux determinations. A consistently positive benthic flux for soluble reactive phosphorus (SRP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 51 publications
6
33
1
Order By: Relevance
“…The present study extends and builds on previous nutrient-transport studies focused on the adjacent lake [16] by posing the following five hypotheses. We used this opportunity to investigate the multiyear temporal changes in the chemistry and biology that occur to the benthos and water column after this approach to wetland restoration was implemented.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…The present study extends and builds on previous nutrient-transport studies focused on the adjacent lake [16] by posing the following five hypotheses. We used this opportunity to investigate the multiyear temporal changes in the chemistry and biology that occur to the benthos and water column after this approach to wetland restoration was implemented.…”
Section: Introductionmentioning
confidence: 54%
“…These changes have transformed the lake to a hypereutrophic status with massive, summer cyanobacterial blooms dominated by the nitrogen-fixing Aphanizomenon flos-aquae [23]. Because the growth of these blooms is supported by the flux of nutrients-phosphorus in particular but potentially other macro-and micronutrients as well-from the lakebed [16], the contribution of the benthos in the newly flooded wetlands to the overall nutrient balance is of considerable interest. As the bloom declines and cells senesce in late July to early August, oxygen may be depleted in the water column and lakebed.…”
Section: Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, previous work showed depletion in dissolved iron concentrations by the end of the late-season (Aug) bloom period, relative to early season conditions (Apr-May; Kuwabara et al 2009). Iron is known to promote microcystin production in other systems (Sevilla et al 2008, Alexova et al 2011, so the seasonal depletion observed in 2006 may signify a possible role for iron availability in microcystin occurrence in Upper Klamath Lake.…”
mentioning
confidence: 87%